Sleep–wake disturbances in cancer patients: narrative review of literature focusing on improving quality of life outcomes - Dickerson SS (Dove Medical Press, 2014)
Suzanne S Dickerson, Laurie M Connors, Ameera Fayad, Grace E Dean School of Nursing, State University of New York, University at Buffalo, NY, USA Purpose: Evidence suggests a high prevalence of sleep–wake disturbances in patients with cancer, occurring at diagnosis, during treatment, and continuing to survivorship. Yet associations between sleep–wake disturbances and the impact on quality of life outcomes is less clear. The purpose of this narrative review of the literature is to evaluate sleep–wake disturbances in patients with cancer, to describe the influence of poor sleep on quality of life as an outcome, and to evaluate the evidence to recommend future interventions. Framework and methods: This review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Four databases (CINAHL, MEDLINE, PsycINFO, and Embase) were searched using terms "cancer OR neoplasm", "sleep, sleep disturbance, sleep disorders or insomnia", and "quality of life"; the search included all years, English language, and peer-reviewed articles on research studies. Studies included measurements of sleep and quality of life in cancer patients at a minimum of two time points and demonstrated relationships between sleep and quality of life. Data were collected on date, patient demographics, cancer type and treatment, timeframe, design, measurement, variables, and results. Results: This narrative review demonstrates that sleep–wake disturbance is a major problem/symptom in patients with cancer. Of the 18 studies included, measurement of sleep-related variables included objective and subjective measures; however, direct measurement of the associations between sleep and quality of life was not common. Cognitive behavioral therapy for insomnia and mind–body interventions demonstrated feasibility when implemented into cancer care settings. In addition, the majority of interventions exhibited moderate effectiveness in improving sleep–wake disturbance and quality of life outcomes. Conclusion: The studies predominantly reported that poor sleep negatively impacts quality of life. The intervention studies included nonpharmacologic interventions such as cognitive behavioral treatment and mind–body and exercise interventions with moderate-to-high levels of evidence for improvement in sleep measures and quality of life. Keywords: sleep–wake disturbance, quality of life, cancer, cognitive behavioral therapy, mind-body interventions, insomnia